Comparison of the safety and immunogenicity of a novel Matrix-M-adjuvanted nanoparticle influenza vaccine with a quadrivalent seasonal influenza vaccine in older adults: a phase 3 randomised controlled trial. Issue 1 (January 2022) - Shinde, Vivek; Cho, Iksung; Plested, Joyce S; Agrawal, Sapeckshita; Fiske, Jamie; Cai, Rongman; Zhou, Haixia; Pham, Xuan; Zhu, Mingzhu; Cloney-Clark, Shane; Wang, Nan; Zhou, Bin; et al.
Summary: Background: Improved seasonal influenza vaccines for older adults that can induce broadly cross-reactive antibodies and enhanced T-cell responses, particularly against A H3N2 viruses, while avoiding egg-adaptive antigenic changes, are needed. We aimed to show that the Matrix-M-adjuvanted quadrivalent nanoparticle influenza vaccine (qNIV) was immunologically non-inferior to a licensed, standard-dose quadrivalent inactivated influenza vaccine (IIV4) in older adults. Methods: This was a phase 3 randomised, observer-blinded, active-comparator controlled trial done across 19 US community-based clinical research sites during the 2019–20 influenza season. Participants were clinically stable and community-dwelling, aged at least 65 years, and were randomised in a 1:1 ratio using an interactive web response system to receive a single intramuscular dose of qNIV or IIV4. The primary objective was to describe safety and show that qNIV was immunologically non-inferior to IIV4. The primary outcomes were adverse events by treatment group and comparative haemagglutination-inhibiting antibody responses (assayed with egg-propagated virus) on day 28, summarised in terms of the ratio of geometric mean titres (GMTRqNIV/IIV4 ) and seroconversion rate (SCR) difference between participants receiving qNIV or IIV4 for all four vaccine homologous influenza strains. The immunogenicity outcome was measured in the per-protocol population. Non-inferiority was shown if the lower bound of the two-sided 95% CI on the GMTRqNIV/IIV4 was at least 0·67 and the lower bound of the two-sided 95% CI on the SCR difference - was at least −10%. The study is registered with clinicaltrials.gov, NCT04120194, and is active and not recruiting. Findings: 2742 adults were assessed for eligibility and 2654 were enrolled and randomised between Oct 14, 2019, and Oct 25, 2019; 1333 participants were randomised to the qNIV group and 1319 to the IIV4 group (two participants withdrew consent before being assigned to a group). qNIV showed immunological non-inferiority to IIV4: GMTRqNIV/IIV4 for the four vaccine homologous influenza strains was A/Brisbane 1·09 (95% CI 1·03 to 1·15), A/Kansas 1·19 (1·11 to 1·27), B/Maryland 1·03 (0·99 to 1·07), and B/Phuket 1·23 (1·16 to 1·29); and SCR difference was A/Brisbane 5·0 (95% CI 1·9 to 8·1), A/Kansas 7·3 (3·6 to 11·1), B/Maryland 0·5 (−1·9 to 2·9), and B/Phuket 8·5 (5·0 to 11·9). 659 (49·4%) of 1333 of participants in the qNIV group and 551 (41·8%) of 1319 participants in the IIV4 group had at least one treatment-emergent adverse event. More solicited adverse events were reported by participants in the qNIV group (551 [41·3%] of 1333) than in the IIV4 group (420 [31·8%] of 1319), and were comprised primarily of mild to moderate transient injection site pain (341 [25·6%] in the qNIV group vs 212 [16·1%] in the IIV4 group). Interpretation: qNIV was well tolerated and produced qualitatively and quantitatively enhanced humoral and cellular immune response in older adults compared with IIV4. qNIV might enhance the effectiveness of seasonal influenza vaccination, and future studies to show clinical efficacy are planned. Funding: Novavax.